Designing a Dress-Up Game as a Media for Introducing Fashion Styles to Generation Z Women - Puji Rahmah Shalih; Dion Darsa Sabrian; Wening Gilang Nawangi (CV. AFDIFAL MAJU BERKAH, 2026)
The development of digital technology has driven innovation in various fields, including fashion. One such technology is interactive media in the form of dress-up games, simulation-based games and visual customization that allow users to explore fashion styles virtually. Dress-up games have the potential to be a medium for introducing clothing styles because they integrate visual elements, interaction, and creativity into one digital experience, one of which is the popularity of the Infinity Nikki game in 2024. On the other hand, women in Generation Z are among the fashion consumers who actively follow trends but still show minimal variations in the level of knowledge in certain clothing styles. Therefore, interactive media that is interesting, creative, and in accordance with the characteristics of Generation Z is needed. This study aims to design a dress-up game as a medium for introducing clothing styles for Generation Z women in the hope that it can help them to get to know clothing styles more fun and effectively.